Effectiveness of Larva Monitoring Training on Knowledge of Dengue Hemorragic Fever Control among Primary School Students in Sibolga, North Sumatera - Wandi Damanik; Nurmaini Nurmaini; Kintoko Rochadi (Masters Program in Public Health, 2019)
Background: Dengue hemorrhagic fever (DHF) is one of the most important public health problems in tropical developing countries. It also has major economic and societal consequences. This study aimed to assess the effectiveness of larva monitoring training on knowledge of dengue hemorrhagic fever control among primary school students in Sibolga, North Sumatera.Subjects and Method: This was a quasi-experiment before and after with no controlled design. The study was conducted in elementary school in Sibolga, North Sumatera, in 2018. A sample of 30 students was selected for this study and received training on DHF for four days. The training employed leaflet and video. The dependent variable was know